A Cross-sectional Study of Depressive Symptoms and Diabetes Self-care in African Americans and Hispanics/Latinos With Diabetes: The Role of Self-efficacy. (August 2016) - Hernandez, Rosalba; Ruggiero, Laurie; Prohaska, Thomas R.; Chavez, Noel; Boughton, Seth W.; Peacock, Nadine; Zhao, Weihan; Nouwen, Arie
Purpose: The purpose of this study is to examine the relationship between depressive symptoms and diabetes self-care in African American and Hispanic/Latino patients with type 2 diabetes and whether the association, if any, is mediated by diabetes-related self-efficacy. Methods: The sample included self-report baseline data of African American and Hispanic/Latino patients with type 2 diabetes who were aged ≥18 years and enrolled in a diabetes self-management intervention study. Depressive symptoms were assessed with the 9-item Patient Health Questionnaire. The Summary of Diabetes Self-care Activities measured engagement in healthy eating, physical activity, blood glucose checking, foot care, and smoking. The Diabetes Empowerment Scale–Short Form assessed diabetes-related psychosocial self-efficacy. Indirect effects were examined with the Baron and Kenny regression technique and Sobel testing. Results: Sample characteristics (n = 250) were as follows: mean age of 53 years, 68% women, 54% African American, and 74% with income <20 000. Depressive symptoms showed a significant inverse association with the self-care domains of general diet, specific diet, physical activity, and glucose monitoring in the African American group. In Hispanics/Latinos, depression was inversely associated with specific diet. Self-efficacy served a significant mediational role in the relation between depression and foot care among African Americans. Conclusions: Self-efficacy mediated the relationship between depression and foot care in the African American group but was not found to be a mediator of any self-care areas within the Hispanic/Latino group. In clinical practice, alleviation of depressive symptoms may improve self-care behavior adherence. Diabetes education may consider inclusion of components to build self-efficacy related to diabetes self-care, especially among African American patients.